GUSDURIAN COMMUNITY AS AN AGENT OF HUMANITY VALUES SOCIALIZATION AND RELIGIOUS MODERATION IN BANDAR LAMPUNG - Ellia Kurnia Ningsih; Siti Badiah; Luthfi Salim; Ahmad Isnaeni (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2026)
This study investigates the role of the Gusdurian Community in Bandar Lampung as an agent for promoting humanitarian values and religious moderation within a multicultural society. The research is prompted by increasing challenges posed by intolerance, social exclusivism, and the diminishing observance of humanitarian values in contemporary social contexts. The study analyzes the mechanisms by which the Gusdurian Community internalizes and disseminates the values of humanity, tolerance, and religious moderation through social activities and interfaith dialogues in Bandar Lampung City. A qualitative case study approach was employed, with data collected via participant observation, semi-structured interviews, and documentation involving community leaders, active members, and public participants in Gusdurian activities. Data analysis utilized the interactive model developed by Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings demonstrate that the Gusdurian Community of Bandar Lampung plays a significant role in advancing humanitarian values and religious moderation through interfaith dialogue, Gus Dur Thought Classes (Indonesian: Kelas Pemikiran Gus Dur/KPG), social initiatives, public discussions, and humanitarian programs. These activities foster religious tolerance, social solidarity, empathy, and harmonious interfaith relations within the city's multicultural society. However, the community faces both internal and external challenges in program implementation, including variations in members' backgrounds and personal commitments that affect participation, as well as limited financial resources that necessitate adjustments based on available funding.